1998
DOI: 10.2307/1389566
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Status, Gender, Group Size, and Emotion in Face-to-Face Groups

Abstract: In two experiments, we investigated the emotional reactions of group members in typical face-to-face interaction on different tasks. Results from both experiments supported the proposition that high-status group leaders would report more positive emotional reactions to group work than would non-leaders. We also found that women reported more positive emotion than men. Unexpectedly, we also found that women leaders were rated more likable than other group members while men leaders were not. As expected, leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 41 publications
2
26
1
Order By: Relevance
“…In a laboratory study conducted by Lovaglia and Houser (1996), higher-status task leaders reported more positive emotion than lower-status group members. This finding has been replicated in other studies (Lucas 1999;Lucas and Lovaglia 1998) and is consistent with affect control theory, which predicts that people experience positive emotion when they enact valued (i.e., good and powerful) role identities (Smith-Lovin 1990). Lovaglia and Houser's research also clarifies the idea that the desire for status operates through inborn emotional tastes (see, e.g., Frank 1988).…”
Section: Explaining Collective Validationsupporting
confidence: 82%
“…In a laboratory study conducted by Lovaglia and Houser (1996), higher-status task leaders reported more positive emotion than lower-status group members. This finding has been replicated in other studies (Lucas 1999;Lucas and Lovaglia 1998) and is consistent with affect control theory, which predicts that people experience positive emotion when they enact valued (i.e., good and powerful) role identities (Smith-Lovin 1990). Lovaglia and Houser's research also clarifies the idea that the desire for status operates through inborn emotional tastes (see, e.g., Frank 1988).…”
Section: Explaining Collective Validationsupporting
confidence: 82%
“…There is no consistent evidence in the literature that suggests that this type of dominance behavior will generate differences in perceptions of leadership between men and women. Although a number of studies have found that women who displayed assertive leadership behavior in task groups were judged more negatively than were their male counterparts (e.g., Butler & Geis, 1990;Eagly, Makhijani, & Klonsky 1992), these findings are at best mixed, with more recent studies finding no differences in perceptions of men and women in leadership roles (e.g., Lucas & Lovaglia, 1998). Therefore, our predictions regarding the consequences of interruption behavior for emergent leadership rankings do not differ for men and women.…”
Section: Proportional Representation and Power Displayscontrasting
confidence: 57%
“…Demographic factors may influence individuals' experience of team member affect and perceptions of TMX (Lucas & Lovaglia, 1998). Given these influences, gender, age, and work experience with team members were also included as controls (Williams, Parker, & Turner, 2007).…”
Section: Control Variablesmentioning
confidence: 99%